Curadoria de conteúdo e atividade docente: perspectivas, práticas e precarização do trabalho docente nos cursos de bacharelado em Jornalismo de universidades públicas de Minas Gerais - Araujo, Leandro Luiz de (2024)
This research covers three different themes that intersect in the journey of higher education teachers: information overload, content curation, and the precariousness of this professional's activity. Through the main question of the investigation “How can content curation in the educational process, driven by information overload, contribute to the precariousness of teaching work in higher education?”, the research delves into its general objective of describing the knowledge and use of curation in teaching work in higher education in undergraduate Journalism courses at three federal universities. In addition, it reflects on information overload and the precariousness of teaching work. When we consider today's society, dominated by the capitalist system that intensely encourages accumulation and excess, we can reflect that the technological innovations of recent decades have also contributed to the formation of information overload. According to Bhaskar (2020), the amount of data present in the digital world practically doubles every three years. For Antunes (2018), technological development also acts to make several professional activities more precarious, adding changes to human labor and contributing to the tension in labor relations. Thus, we deepen our reflections on the advancement of capital, driving technological evolution and leading to changes in the ways of producing, consuming, and sharing information and content. Considering the current situation of information abundance, higher education professionals consequently need to filter and process the materials that will be developed in class, mostly dispersed in digital environments. The development of multiple activities becomes a reality in the exercise of teaching, also demanding more cognitive and physical effort and time from education professionals outside the classroom. The work of the teacher goes beyond the walls of the classroom by requiring research, planning, reflection, and constant professional updating to carry out activities interrelated to pedagogical dialog. Hypolito, Vieira and Pizzi (2009) characterize the different forms aimed at the intensification and consequent precariousness of teaching work as situations that reduce the time for rest in the workday, increase work overload and introduce technical solutions that reduce the space for planning. Thus, for its implementation, this research adopts conceptual deepening through bibliographic and documentary research; field survey through descriptive data collection technique; and, finally, the refinement, analysis and conflict of data through the comparative approach and perspective of historical-dialectical materialism.